Relational interventions in psychotherapy: development of a therapy process rating scale - Ulberg, Randi (BMC Psychiatry, 2016)
BACKGROUND: In psychodynamic psychotherapy, one of the therapists’ techniques is to intervene on and encourage exploration of the patients’ relationships with other people. The impact of these interventions and the response from the patient are probably dependent on certain characteristics of the context in which the interventions are given and the interventions themselves. To identify and analyze in-session effects of therapists’ techniques, process scales are used. The aim of the present study was to develop a simple, not resource consuming rating tool for in-session process to be used when therapists’ interventions focus on the patients’ relationships outside therapy. METHODS: The present study describes the development and use of a therapy process rating scale, the Relational Work Scale (RWS). The scale was constructed to identify, categorize and explore therapist interventions that focus on the patient’s relationships to family, friends, and colleges Relational Interventions and explore the impact on the in-session process. RWS was developed with sub scales rating timing, content, and valence of the relational interventions, as well as response from the patient. For the inter-rater reliability analyzes, transcribed segments (10 min) from 20 different patients were scored with RWS by two independent raters. Two clinical vignettes of relational work are included in the paper as examples of how to rate transcripts from therapy sessions with RWS. RESULTS: The inter-rater agreement on the RWS items was good to excellent. CONCLUSION: Relational Work Scale might be a potentially useful tool to identify relational interventions as well as explore the interaction of timing, category, and valence of relational work in psychotherapies. The therapist’s interventions on the patient’s relationships with people outside therapy and the following patient-therapist interaction might be explored. TRIAL REGISTRATION: First Experimental Study of Transference-interpretations (FEST307/95) Registration number: ClinicalTrials.gov Identifier: NCT00423462. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-016-1021-4) contains supplementary material, which is available to authorized users.